Effect of quercetin on estrogen receptor α and β expression in uterine tissues in ovariectomized rats: quercetin regulated uterine estrogen receptor expression - Zhao, Chunzhen; Wang, Lin; Wang, Shumei; Guo, Xiaofan; Li, Haijian; Lv, Yanna (Journal of Biomedical and Pharmaceutical Research, 2018)
`Objective To explore the effect of quercetin on mRNA expressions of estrogen receptor α (ERα) and estrogen receptor β (ERβ) in ovariectomized (OVX) Sprague-Dawley (SD) rats. Method Thirty-two SD rats were randomly divided into 4 groups: sham group, ovariectomy group, quercetin group and estradiol group. The mRNA expression of ERα and ERβ in the uterus were determined by RT-PCR. The level of estradiol (E2) in the plasma was detected by ELISA. Results After ovariectomy, uterus coefficient, serum estradiol level and the mRNA expression of ERα and ERβ in the uterus were markly decreased in OVX rats. After treatment with quercetin, uterus coefficient, serum estradiol level and the mRNA expression of ERα and ERβ in the uterus were significantly increased. Conclusion Quercetin can improve menopausal syndrome in the OVX rats through regulating estrogen release and receptor expression.